Legal analysis of the authority of quarantine officials in handling illegal cattle importation - Yulia Hardhiyanti Putri; Soerya Respationo; Erniyanti Erniyanti; Parameshwara Parameshwara (Annals of Justice and Humanity, 2022)
Purpose: The purpose of this study is to determine the implementation of the Quarantine Officer's authority in handling illegal cattle importation, and what are the obstacles and solutions to the Quarantine Officer's authority in handling illegal cattle importation. Research Methodology: The research method used in this study is the normative research method by involving the analysis of legal regulations, policies, and legal instruments related to applicable laws and regulations. Results: The results show that the implementation of Quarantine Officers in conducting quarantine supervision and actions at the Batam Class I Agricultural Quarantine Center is in accordance with applicable procedures and laws. Implementation: The implementation of quarantine according to Law Number 21 of 2019 is the authority of the Central Government and to achieve its objectives, quarantine measures and supervision and/or control of carrier media are carried out. There are two officials who are given duties and responsibilities in the implementation of quarantine, namely Quarantine Officials (consisting of Animal Quarantine Officials, Plant Quarantine Officials and Fish Quarantine Officials) and Civil Servant Investigators (PPNS)/Quarantine Investigators. Obstacle factors faced include: weak sanctions or penalties for violators in the field of quarantine regulations. Quarantine officials may conduct intelligence activities in coordination with the agency responsible for state intelligence and/or other agencies that perform intelligence functions. It should be clear when and what quarantine measures are taken by Quarantine Officers with Quarantine Investigators. The long process in the regulation of document processing is not balanced with the rate of need for animal entry.